2017
DOI: 10.1007/s40093-017-0154-x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient uptake and growth of spinach as affected by cow manure co-composted with poplar leaf litter

Abstract: Purpose Wastes were composted and applied as the soils amendment to improve soil fertility and crop productivity. The study aimed at assessing the nutrient uptake and growth of spinach (Spinacia oleracea L.) grown in soils amended with cow manure after a co-composting process. Methods Sandy loam and silt loam soils were amended with cow manure after co-composting with poplar leaf litter at 1:0, 1:1, 1:2 and 1:3. The compost was applied to soil at the rate of 20 t ha -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…that stimulate the activity of methanogenic species but is low in energetic value. 42 The codigestion of CM and OFSMW is therefore promising to obtain enhanced biogas yields.…”
Section: Introductionmentioning
confidence: 99%
“…that stimulate the activity of methanogenic species but is low in energetic value. 42 The codigestion of CM and OFSMW is therefore promising to obtain enhanced biogas yields.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, organics increase surface charge and area and number of exchange sites in the soil, thereby reducing metal mobility by surface adsorption (32) and stable complexation (33). Carbon compounds are the main constituents of organic amendments which are involved in metal precipitation and their conversion to stable forms (34). Xiong et al investigated the effect of nano-zeolite on chemical fractions of Cd in soil and its uptake by cabbage and concluded that the plant biomass was significantly increased by Nano zeolite.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the total biomass of rice plants obtained at the end of the experiment was higher in treatments with cattle manure compost [33]. In another study, dried spinach biomass increased significantly after applying compost obtained from cattle manure and poplar leaves [34].…”
Section: Dry Biomass Of Autumn Barley Plantsmentioning
confidence: 92%
“…From the results presented in another study, where was used compost from cattle manure in mixture with inorganic fertilizer, and inorganic fertilizer, it appears that the pH and the electrical conductivity of the soil increased significantly in the treatments with cattle manure compost [40]. The increase of the electrical conductivity of the soil can be attributed to a large amount of soluble cations in the compost and their release into the soil [34].…”
Section: Soil Phmentioning
confidence: 98%